ответ:3*9^(x-1/2)-7*6^x + 3*4^(x+1)=0
3*9^x*9^(-1/2)-7*6^x+3*4^x*4=0
9^(-1/2)=1/3, 3*(1/3)=1, 3*4=12
9^x-7*6^x+12*4^x=0,
т.к. 4^x≠0 поделим обе части уравнения на это выражение
(9/4)^x-7*(3/2)^x+12=0
пусть (3/2)^x=y, тогда уравнение примет вид
у^2-7y+12=0, y=3, y=4
(3/2)^x=3 или (3/2)^x=4
x=log(1.5)3 x=log(1.5)4 (1,5 - основание логарифма)
ответ: log(1.5)3 , log(1.5)4
log(1.5)3= log(1.5)(2*1,5)= log(1.5)(1,5)+ log(1.5)2=1+log(1.5)2
1<log(1.5)2<2, 2<1+log(1.5)2<3
log(1.5)3 ∈[2,3]
log(1.5)3<log(1.5)4 < log(1.5)(4 .5)
2<log(1.5)4 < log(1.5)(4 .5)
log(1.5)(4 .5)=log(1.5)(3*1.5)=log(1.5)(1.5)+log(1.5)(3)=1+1+log(1.5)2>3
log(1.5)4 ∉[2,3]
1. 8 3/4-7 2/9=8 27/36-7 8/36=1 19/36
2. 2,25-2 7/9= 2 25/100-2 7/9=2 1/4- 2 7/9=2 9/36-2 28/36=- 17/36
3. 1 19/36+(-17/36)=1 19/36-17/36= 1 2/36=1 1/18